THE PROGRAM OF DEVELOPMENT OF THE SCHOOL AS A CONDITION OF PROVIDING NEW QUALITY OF EDUCATION: THE PROJECT APPROACH - Larisa N. Paskhalova; Irina V. Dolgopolova (Russian State Vocational Pedagogical University, 2015)
The aim of the investigation is to generalize the experience on implementation of the Program of development of educational institution that allows providing high quality of education in the conditions of introduction of Federal Educational Standards of New Generation. Methods. Traditional psychological and pedagogical methods involve: stating, developing and control. Analysis of the average data and dynamics of educational results, an expert estimation, interrogations and questioning are used. Results. Transition of a gymnasium to educational institution of new type has become result of introduction of the Program of development. The unique profile of establishment is created and priority positions are taken in the educational environment of the region; in response to an implementation of the program of the development focused on the social procurement. Efficiency of the Program is confirmed with intermediate results of monitoring concerning all subjects of educational space: trained, teachers and parents. The program allows all participants of educational process to be involved in process of introduction of new quality of education via the mechanism of realization of system. The program represents improvement of activity of structures of educational space of a gymnasium, development of resource base, and also a control system as a factor of ensuring stability of functioning and innovative development of a gymnasium. Scientific novelty. The possibility of implementation of the Program of development of educational institution through introduction of system-activity and project-based approach which connected nine sub-programmes in one complex (structured in three modules) is shown. It includes introduction of Federal State Educational Standard (FSES), an international exam, development of a progymnasium, formation of the personality, ongoing support to gifted children, extension of innovative culture of teachers, efficiency of management and development of organizational system, and also development of culture of school meal. Practical significance. The proposed Program of development is an actual administrative tool which allows teaching staff harmoniously and purposefully to carry out objectives by implementation of the planned projects; also it gives the chance to the customers of social services to estimate objectively achievements of educational institution. This Program is focused on the priorities of the social procurement.